Z '(B-L) phenomenology at the LHC - Coutinho, Y. A.; Fortes, E. C. F. S. [UNESP]; Montero, J. C. [UNESP] (Amer Physical Soc, 2011)
We study the Z' phenomenology for two extensions of the electroweak standard model (SM) which have an extra U(1)(B-L) gauge factor. We show the capabilities of the LHC in distinguishing the signals coming from these two extensions and both of them from the SM background. In order to compare the behavior of these B - L models we consider the reaction p + p -> mu(+) + mu(-) + X and compute some observables as the total cross sections, number of events, forward-backward asymmetry, final particle distributions like rapidity, transverse momentum, and dimuon invariant mass, for two LHC regimes: root s(L) = 7 TeV (1 fb(-1)) and 14 TeV (100 fb(-1)) for M-Z' = 1000 GeV and 1500 GeV. We show that by using appropriate kinematic cuts some of the observables considered here, we are able to extract different properties of the Z' boson, and hence to provide information about to which B - L model it belongs to.